(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-1-59-71 The article addresses similarities and differences of phraseological verbalization of the notion labour in the English and Russian worldviews. The objective of the article is to identify and describe the similarities and differences of phraseological verbalization of the notion labour in the English and Russian worldviews. Semantic and linguoculturological features of 62 English and 106 Russian phraseological units constituting the empirical corpus have been considered. The similarity manifests itself in such semantic features as to work hard, hard work, a quality of being laborious, the result of work, labour as virtue. The semantic volume of labour phraseological representation is broader in English as compared with Russian. Gender-marked phraseological units and phraseological units representing the forced nature of labour are traced in the Russian language. The corpus analysis indicates that phraseological units perform the function of hyperbolization and intensity, the expressive, figurative, and summarizing functions. Phraseological units serve as cultural standards and symbols associated with labour. Key words: value, labour, phraseological unit, semantic volume, cultural code, standard, stereotype Acknowledgements: the research was conducted on the topic of the state assignment “Decoding and interpretation of axiological semantics in Slavic, Germanic, Romance and Caucasian linguistic culturesˮ (state registration number 124012400351-9).